Genetic association, mRNA and protein expression analysis identify ATG4C as a susceptibility gene for Kashin–Beck disease. Issue 2 (February 2017) - Wu, C.; Wen, Y.; Guo, X.; Yang, T.; Shen, H.; Chen, X.; Tian, Q.; Tan, L.; Deng, H.-W.; Zhang, F.
Summary: Objective: Recent study observed defective autophagy in chondrocytes with Kashin–Beck Disease (KBD). To clarify the potential role of autophagy-related ATG4C gene in the development of KBD, we conducted an integrative analysis of genetic association, messenger ribonucleic acid (mRNA) and protein expression of ATG4C in KBD patients. Methods: 1026 subjects (559 KBD patients and 467 healthy cases) were enrolled in discovery association study. Four single nucleotide polymorphisms (SNPs) of ATG4C gene (rs11208030, rs4409690, rs12097658 and rs6587988) were genotyped by Sequenom MassARRAY platform. Association analysis was conducted by PLINK software. The significant SNPs of ATG4C were replicated using an independent sample of 899 subjects (including 90 KBD patients and 809 healthy controls). Ungenotyped SNPs in ATG4C gene were imputed by IMPUTE 2.0. Knee cartilage specimens were collected from five KBD patients and five healthy subjects. Quantitative real-time polymerase chain reaction (qRT-PCR) and western blot were performed to compare the mRNA and protein expression levels of ATG4C between KBD cartilage and control cartilage. Results: We observed significant association between KBD and rs11208030 ( P value = 0.003), rs4409690 ( P value = 0.004), rs12097658 ( P value = 0.003) and rs6587988 ( P value = 0.003) in both discovery and replication samples. The mRNA expression level of ATG4C (ratio = 0.168, P value = 0.007) in KBD chondrocytes was significantly lower than that in normal chondrocytes. Western blot ( P value < 0.001) further confirmed the reduced expression of ATG4C protein in both KBD cartilage and chondrocytes. Conclusion: Our results strongly suggest that ATG4C was a novel autophagy-related susceptibility gene of KBD.